Study of Petrogenesis, Modeling And Involved Fluids in Igneous Rocks in The area of Tanurjeh Deposit (Revista Geoaraguaia, 2021)
Tanurjeh porphyry copper-gold deposit is located in Khorasan Razavi province, south of Neishabour and 5 km south of Tanurjeh village. The types of rocks in the study area include andesite, porphyry diorite, quartz porphyry diorite, porphyry granodiorite, rhyolite, rhyodacite and tuff, and metal minerals include magnetite, chalcopyrite, pyrite, iron oxides and hydroxides, covellite, malachite, galena, sphalerite, malachite, rutile and gold particles. To accurately detect copper and gold anomalies from the field, the fractal geometry-number method was used. A combination of exploratory layers was performed to identify suitable areas for exploratory drilling. To determine the temperature of the deposit formation and its chemical properties, salinity of the trapped fluids was taken. Evaluation of the involved fluids indicates that the primary fluids have high salinity and the secondary fluids have medium salinity and primary fluids homogenize at 319 to 514 ° C and secondary fluids at 138 to 345 ° C. These results show the mineralization of copper and gold in terms of porphyry system type and mineralization can continue to depths of more than 350 meters. However, the absence of stock quartz veins, the presence of a large siliceous zone and the lack of mineralization of copper are some of the things that make a difference compared to porphyry copper systems. As a result, this area can be considered as a porphyry copper-gold mineralization area in which mineralization has been done in depth and in the vicinity of the intrusion mass and in some places points are seen as streaks on the surface.